Voluntary Ethanol Consumption Induced by Social Isolation Reverses the Increase of α4/δ GABAA Receptor Gene Expression and Function in the Hippocampus of C57BL/6J Mice - Sanna, Enrico; Talani, Giuseppe; Obili, Nicola; Mascia, Maria Paola; Mostallino, Maria Cristina; Secci, Pietro Paolo; Pisu, Maria Giuseppina; Biggio, Francesca; Utzeri, Cinzia; Olla, Pierluigi; Biggio, Giovanni; Follesa, Paolo (Frontiers in Neuroscience, 2011)
Post-weaning social isolation (SI) is a model of prolonged mild stress characterized by behavioral and neurochemical alterations. We used SI in C57BL/6J mice to investigate the effects of ethanol (EtOH) in the free-choice drinking paradigm on gene expression and function of -aminobutyric acid type A receptors (GABAARs) and on the role of neuroactive steroids in the actions of EtOH in the hippocampus. SI stress induced a marked reduction in hippocampal 3α-hydroxy-5α-pregnan-20-one (3α,5α-TH PROG) and was associated with molecular and functional changes of the GABAAR. The gene expression of the α4 and δ subunits was increased in the hippocampus of SI C57BL/6J mice; the expression of the γ2 subunit was decreased whereas that of the α1 did not change. Patch clamp recordings in dentate gyrus (DG) granule cells obtained from SI C57BL/6J mice revealed a greater enhancement of tonic currents induced by α-(4,5,6,7-tetrahydroisoxazolo[5,4-c] pyridin-3-ol (THIP) compared to that in control C57BL/6J mice. These neurochemical, molecular and functional changes observed in SI C57BL/6J mice were associated with an increased EtOH intake and EtOH preference. Nevertheless, the increase in EtOH consumption did not restore the reduction in hippocampal 3α,5α-TH PROG induced by SI. EtOH self-administration blocked the changes in gene expression of the α4 subunit but not those of the δ and γ2 subunits induced by SI. In addition, EtOH self-administration did not block the SI-induced changes in GABAAR-mediated tonic inhibition in hippocampal granule cells but increased the frequency of basal GABAergic sIPSCs in DG granule cells. We conclude that self-administration of EtOH selectively abolishes the increase α4 receptor subunits but not other neurochemical, molecular and functional modifications induced by SI prolonged mild stress.